Implementasi Program Generasi Berencana dalam Penanganan Pernikahan Anak di Kabupaten Temanggung - Arum Pratiwi; Ismi Dwi Astuti Nurhaeni (Jurnal Mahasiswa Wacana Publik, 2022)
This research aims to analyze the implementation of GenRe program in Temanggung Regency by using Van Meter and Van Horn policy implementation model. Descriptive Qualitative method is used to analyze the implementation of GenRe program in Temanggung Regency. Data collection was conducted through observation, interview, and documentation. Data in this research are in the form of primary data, namely the result of interview process, and secondary data, namely additional data found during observation and interview. Meanwhile, the data processing is carried out by interactive data analysis, namely data reduction, data presentation, and drawing conclusion. This study shows that the implementation of GenRe program in Temanggung Regency is carried out properly according to the standards and objectives set, has adequate resource, has carried out inter organizational communication, the existence of non- organizational characteristics which are not hierarchical and participatory, has environmental influences, and has positive attitude towards program implementing agents. The implementations of GenRe program are influenced by six interrelated variables and consist of the driving factors and inhibiting factors for program implementations.